Novel point mutations and mutational complexes in the enhancer II, core promoter and precore regions of hepatitis B virus genotype D1 associated with hepatocellular carcinoma in Saudi Arabia. Issue 12 (9th July 2013) - Khan, Anis; Al Balwi, Mohammed A.; Tanaka, Yasuhito; Hajeer, Ali; Sanai, Faisal M.; Al Abdulkarim, Ibrahim; Al Ayyar, Latifah; Badri, Motasim; Saudi, Dib; Tamimi, Waleed; Mizokami, Masashi; Al Knawy, Bandar
<x xml:space="preserve">Abstract</x> In this study, a cohort of 182 patients [55 hepatocellular carcinoma (HCC) and 127 non‐HCC] infected with hepatitis B virus (HBV) in Saudi Arabia was investigated to study the relationship between sequence variation in the enhancer II (EnhII), basal core promoter (BCP) and precore regions of HBV genotype D (HBV/D) and the risk of HCC. HBV genotypes were determined by sequencing analysis and/or enzyme‐linked immunosorbent assay. Variations in the EnhII, BCP and precore regions were compared between 107 non‐HCC and 45 HCC patients infected with HBV/D, followed by age‐matched analysis of 40 cases versus equal number of controls. Age and male gender were significantly associated with HCC (p = 0.0001 and p = 0.03, respectively). Serological markers such as aspartate aminotransferase, albumin and anti‐HBe were significantly associated with HCC (p = 0.0001 for all), whereas HBeAg positivity was associated with non‐HCC (p = 0.0001). The most prevalent HBV genotype was HBV/D (94%), followed by HBV/E (4%), HBV/A (1.6%) and HBV/C (0.5%). For HBV/D1, genomic mutations associated with HCC were T1673/G1679, G1727, C1741, C1761, A1757/T1764/G1766, T1773, T1773/G1775 and C1909. Age‐ and gender‐adjusted stepwise logistic regression analysis indicated that mutations G1727 [odds ratio (OR) = 18.3; 95% confidence interval (CI) = 2.8–118.4; p = 0.002], A1757/T1764/G1766 (OR = 4.7; 95% CI = 1.3–17.2; p = 0.01) and T1773 (OR = 14.06; 95% CI = 2.3–84.8; p = 0.004) are independent predictors of HCC development. These results implicate novel individual and combination patterns of mutations in the X/precore region of HBV/D1 as predictors of HCC. Risk stratification based on these mutation complexes would be useful in determining high‐risk patients and improving diagnostic and treatment strategies for HBV/D1.